Solid waste monitoring and management using RFID, GIS and GSM - Arebey, Maher; Hannan, M A; Basri, Hassan; Abdullah, Huda (2009 IEEE Student Conference on Research and Development, 2009)
This paper deals with the solid waste monitoring and management system using radio frequency identification (RFID) associate with intelligent systems. The system consists of RFID system, mobile communication like GSM and geographical information system (GIS) for tracking vehicle position. The proposed system would be able to monitor the solid waste collection process and management the overall collection process. It would provide in time solid waste collection, tracking the vehicle position through the GIS database and also overcome the disadvantages such as usage of minimum route, low fuel cost, clean environment and available vehicle. The technologies that would be used in the proposed system are good enough to ensure the practical and perfect for solid waste collection process monitoring and management for green environment.